The manor house : a novel [compact disc, unabridged] - Macmillan, Gilly (HarperCollins, 2023)
Childhood sweethearts Nicole and Tom are a normal, loving couple, until a lottery win changes their lives. Soon they're living the high life, but then Tom is found dead in the pool. Was it an accident?